2021
DOI: 10.1002/jwmg.22066
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Glucocorticoid Metabolites as Biomarkers in Equids: Assay Choice Matters

Abstract: Free ranging animals are exposed to environmental, demographic, and ecological challenges over time, which can affect their health and fitness. Non-invasive biomarkers can provide insight into how animals cope with these challenges and assess the effectiveness of conservation management strategies. We evaluated how free ranging ponies (Equus ferus caballus) on the Carneddau Mountain range, North Wales respond to 2 stimuli: an acute stressor of an annual roundup event in November 2014, and spatial and temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Before castration, these authors report median concentrations of 10.5 nmol/kg feces (3.19 ng/g 1 ) and after castration values increased to 26.2 (7.97 ng/g 1 ) and 50 nmol/kg feces (15.22 ng/g 1 ). In addition, Hinchcliffe et al 2021 found that fecal glucocorticoid metabolites were elevated from the second day following a stressor (a roundup) and then slowly returned to basal levels over the next 2 weeks. Franceschini et al…”
Section: Methodsmentioning
confidence: 99%
“…Before castration, these authors report median concentrations of 10.5 nmol/kg feces (3.19 ng/g 1 ) and after castration values increased to 26.2 (7.97 ng/g 1 ) and 50 nmol/kg feces (15.22 ng/g 1 ). In addition, Hinchcliffe et al 2021 found that fecal glucocorticoid metabolites were elevated from the second day following a stressor (a roundup) and then slowly returned to basal levels over the next 2 weeks. Franceschini et al…”
Section: Methodsmentioning
confidence: 99%
“…While strict legal enforcement controlling human-animal interactions is necessary to avoid abuse of companion or farm animals (Webster, 2001;Verga and Michelazzi, 2009), these regulations pose challenges with free-roaming animals in more extensive environments (Veit and Browning, 2021). Indeed, while domestic horses habituated to regular veterinary interventions can manage stress well (Carroll, et al 2022), captures and veterinary care may cause acute stress levels in free-roaming horses (Hinchcliffe et al, 2021, Scasta et al, 2021, and endanger their lives (e.g., injuries caused by fear (Winther, 2006)). Medical treatments may also harm horses, (e.g., due to toxicities or reduced immunity, Ang et al 2022;Flood and Stewart, 2022) affecting their shortand long-term life-quality (Rombke et al 2010;van Klink et al 2015).…”
Section: Clashes Of Ethicsmentioning
confidence: 99%